Critical Review and Reality of Religious Moderation in Law and Legal Frameworks in Indonesia - Faozan, Muhammad; Rasyidi, Abdul Haris (Asian Journal of Science, Technology, Engineering, and Art, 2023)
This article aims to conduct a critical review of the role of religious moderation in the context of legislation and the legal framework in Indonesia. Through in-depth analysis, this article investigates the impact of legislative changes on the implementation of religious moderation and its relevance in building a strong and effective legal framework to support harmony in diversity in Indonesia. This research uses qualitative methods with content analysis techniques, namely reviewing and analyzing a number of literature related to the subject matter using a document analysis approach to examine laws and regulations related to religious moderation in Indonesia. Document analysis is used to analyze the text of legislative regulations by understanding their substance, objectives and impact on religious moderation. Meanwhile, literature study is understanding the views and concepts of religious moderation from academic, religious and societal perspectives. The reality in the field regarding the challenges of implementing religious moderation, critical analysis of the legal framework and the relationship between law and social reality are some of the results of critical analysis and findings that can be used as references in viewing and understanding religious moderation in the context of Indonesian society.